2008
DOI: 10.1590/s2236-89062008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Species richness of arbuscular mycorrhizal fungi in forests with Araucaria in Southern Brazil

Abstract: -(Species richness of arbuscular mycorrhizal fungi in forests with Araucaria in Southern Brazil). This study aimed to characterize species richness of arbuscular mycorrhizal fungi (AMF) in three distinct forests with Araucaria angustifolia (native forest, reforestation with A. angustifolia and plantation with Pinus taeda) in the "Floresta Nacional de São Francisco de Paula", State of Rio Grande do Sul, also accounting for seasonal variation. Six soil samples from each forest were collected from Araucaria angus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
1
6
1
4
Order By: Relevance
“…Carneiro et al (2009) also found lower sporulation under native vegetation of Cerrado, for both sandy soil, similar to that of the present study, and clayey soil. A similar pattern was also observed by Sturmer & Siqueira (2011) in the Amazon biome, by Lima et al (2007) in areas of Caatinga and Zandavalli et al (2008) in Araucaria forests in Southern Brazil. According to Lima et al (2007), the negative anthropic interference has different effects in the study on variations in each system; while the increase in degradation level stimulated AMF multiplication in areas of native vegetation, the opposite effect occurred in crop areas.…”
Section: Resultssupporting
confidence: 82%
“…Carneiro et al (2009) also found lower sporulation under native vegetation of Cerrado, for both sandy soil, similar to that of the present study, and clayey soil. A similar pattern was also observed by Sturmer & Siqueira (2011) in the Amazon biome, by Lima et al (2007) in areas of Caatinga and Zandavalli et al (2008) in Araucaria forests in Southern Brazil. According to Lima et al (2007), the negative anthropic interference has different effects in the study on variations in each system; while the increase in degradation level stimulated AMF multiplication in areas of native vegetation, the opposite effect occurred in crop areas.…”
Section: Resultssupporting
confidence: 82%
“…Previous studies indicated that araucaria is capable of supporting AMF symbiosis with a greater number of different fungal species [11,[22][23][24][25] than that we found in this experiment. To date, araucaria AMF spore richness varied from 8 [23] to 13 [11] in forests of the State of Rio Grande do Sul and from 26 [24] to 58 [25] in forests of Sao Paulo. The variation in spore AMF richness has been frequently attributed to heterogeneity in soil habitat and to the variable capacity of AMF species to adapt to climate and soil in different regions [10,13].…”
Section: Discussioncontrasting
confidence: 47%
“…Pioneer studies already reported AMF in fine araucaria roots [9]; however, it was only recently that the AMF has been considered as a strategy to increase araucaria growth under nursery conditions [10,11]. In fact, the studies performed so far show two important facts: first, that araucaria is colonized by a large and diverse number of AMF species [10,12]; and second that the araucaria positively respond to inoculation of some AMF species, both in high and low P supply [13].…”
Section: Introductionmentioning
confidence: 99%
“…A. foevata was found in areas of commercial reforestation of Pinus taeda (Zandavalli et al, 2008), in areas with Eucalyptus grandis Scotti, 2008), E. camaldulensis (Pagano et al, 2009), E. urophylla (Santos et al, 2013). G. macrocarpum occurred in commercial forest species of E. camaldulensis, E. grandis, M. domestica, M. prunifolia, P. taeda and S. virgata, in both monocultures and consortium forest plantations (Table 1).…”
Section: Cernementioning
confidence: 99%